Analisis Penerapan Penagihan Pajak Reklame Dengan Surat Teguran Dalam Upaya Meningkatkan Penerimaan Pajak Daerah Di Unit Pelayanan Pemungutan Pajak Daerah Kecamatan Cilandak Tahun 2019-2022 - Adilah, Dante Apra; Andrayanti, Iin; Prehantio, Tri Waluyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aimed to analyze the implementation of billboard tax billing with a letter of reprimand in order to increase local tax revenue at the regional tax collection service unit in Cilandak sub-district in 2019-2022, also to analyze inhibiting entities and efforts made in the implementation of the billboard tax billing with a letter of reprimand. The phenomena of this research include the non-compliance of billboard taxpayers, the overdue billboard licenses, the mismatch of billboard taxpayers data, the limited financial capacity of billboard taxpayers, the lack of understanding on the regulations and the limited human resources (HR). The research method used was the qualitative with the descriptive research type. In this research, it used data collection methods in form of observations, interviews, and documentations. Data analysis techniques used were data collection, data reduction, data presentation, and conclusion drawing. The result of this study indicated that billboard tax billing with a letter of reprimand at the regional tax collection service unit in Cilandak sub- district had been running in accordance to the existing regulation, however it had not yet run optimally as targeted; thus it had not increase the tax revenue in the regional tax collection service unit in Cilandak sub-district and the socialization program carried out benefited the billboard taxpayers although not all billboard taxpayers knew the aforementioned socialization program. Obstacles occured were the mismatch of billboard taxpayers data, the lack of understanding on the regulations, the limited financial capability, and the limited human resources (HR). Efforts made were increasing education on the billboard taxpayers by conducting socializations on the billboard taxpayers more intensively, utilizing the current technology and increasing the existing resources in the implementation of billboard tax billing with a letter of reprimand.